Status of water quality and level of trophic in Juanda Reservoir of Purwakarta Regency, West Java, Indonesia - Jubaedah Iis (EDP Sciences, 2021)
Juanda reservoir is one of the reservoirs located in Purwakarta Regency, West Java Province, Indonesia, whose primary function is hydropower, water resources for irrigation, industrial and drinking water, and secondary function for fisheries and tourism activities. Currently, an increase in activities around the existing reservoir has affected its water quality. In order to determine the water quality and trophic level status of the Juanda reservoir, research has been conducted within five stations during the period of August-December 2020. The water quality status includes physical, chemical, and biological parameters that compared with Store standards on Class II and III. Meanwhile, the trophic status was determined by Trophic Level Index (TLI) based on the parameters of transparency, chlorophyll-a, total nitrogen, and total phosphorus. The results show that the water quality status of Juanda reservoir has been contaminated Class III and heavily polluted Class II. The parameters that exceed include ammonia, nitrate, and BOD5. The Juanda reservoir's tropic status was in the eutrophic category, with TLI values ranging from 4.6 to 5.2.